Surfactant-free preparation of poly(vinylidene fluoride) nanoparticle dispersions and their use as surface coating agents. Issue 2 (4th January 2018) - Heo, Hyeon Jun; Park, In Jun; Lee, Sang Goo; Ha, Jong-Wook; Lee, Soo-Bok; Sohn, Eun-Ho
Abstract : Surfactant-free emulsion polymerisation of vinylidene fluoride was performed using poly(ethylene glycol) and a dispersion of poly(vinylidene fluoride) (PVDF) nanoparticles instead of typical fluorinated surfactants. Abstract : Surfactant-free emulsion polymerisation of vinylidene fluoride was performed using poly(ethylene glycol) and a dispersion of poly(vinylidene fluoride) (PVDF) nanoparticles instead of typical fluorinated surfactants. This approach allows facile preparation of PVDF-nanoparticle-coated surfaces, thus expanding the application scope of PVDF nanoparticles and their copolymer dispersion products.